The Arctic fury : a novel - Macallister, Greer (Sourcebooks Landmark, 2021)
"1855: Virginia Reeve is summoned by an eccentric Brit with a compelling offer. Lady Jane Franklin wants her to lead a dozen women into the Arctic in search of the ships of her husband's lost expedition, and she's willing to pay handsomely. All four search attempts Lady Franklin has sponsored have failed. She has decided only a radical new approach can succeed: let women make the decisions. Lady Franklin will disavow all knowledge of the expedition if it fails, but if it succeeds, she promises great rewards .A year later, Virginia stands trial for murder. Survivors of the expedition willing to publicly support her sit in the front row. There are only six left."--Provided by publisher.